Implantable biomedical microsystems for neural prostheses. - Stieglitz, T.
In the following article, the technologies to fabricate polyimide-based thin and flexible substrates with monolithically integrated electrode arrays and printed circuit boards (PCB) for hybrid electronic assemblies as well as an assembling technique that connects bare electronic dice with flexible PCBs are presented. The concept of modular, flexible biomedical microsystems as neural prostheses is introduced in general and described in detail in three examples. A cuff electrode with integrated multiplexer circuitry and standard implantable cables represents the combination of microtechnology with precision mechanics; a sieve electrode used as an implant in peripheral nerve regeneration studies demonstrates the next level of integration density but still uses a cable connection; and last, joint effort to fabricate the demonstrator of a vision prosthesis that is completely implantable in the eye with a wireless link for energy supply and data transmission is presented. System design, hybrid assembling technology, and flexible multilayer encapsulation using parylene and silicone rubber are the key components for creating a new generation of neural prostheses for complex and challenging new applications.
Keywords: Bare electronic dice; Cuff electrode; Data transmission; Energy supply; Eye; Flexible multilayer encapsulation; Hybrid assembling technology; Hybrid electronic assemblies; Implantable biomedical microsystems; Integrated multiplexer circuitry; Microtechnology; Modular flexible biomedical microsystems; Monolithically integrated electrode arrays; Neural prostheses; Parylene; Peripheral nerve regeneration; Polyimide-based thin flexible substrates; Precision mechanics; Printed circuit boards; Sieve electrode; Silicone rubber; System design; Vision prosthesis; Wireless link